Métricas de la publicidad-promoción y participación de mercado de las Cajas Municipales de la ciudad de Tarapoto año 2014 - Escudero del Aguila, Cinthia del Pilar (2015)
This research aims obejtivo determine the relationship between metric advertising - promotion and market share of the Municipal Boxes Tarapoto - 2014, through signing techniques, interview and survey of financial information, for the development of this research. It is not Experimental Type since none of the variables under study be manipulated; will be described as it happens the phenomenon and not its reality and descriptive correlational design was altered, because the relationship between !he independent variable and the dependent variable, where the data processing is done through the use of interviews were looking for !he sample obtained so that they keep a relationship with the dimensions and indicators of variables and then are analyzed and tabulated, thus resolving the issues raised , also for the analysis and interpretation of data Excel programs were used , Spss and Word, using tables and graphs. Alter obtaining the results it is concluded that advertising metrics - promotion and market share maintain a high ratio demonstrated statistically by the Pearson correlation, which shows that the significance level is 0.045, so the same test t studen shows that Ho is rejected, il means that having more efficient advertising and promotion of products and services offered studied municipal banks greater market share, increase customer loyalty and increased customer base.